Falsafah ‘Torang Samua’ Ciptaan Tuhan Sebuah Sumbangsih Bagi Moderasi Beragama di Sulawesi Utara - Irvan Nixon Grosman Grosman; Heldy Rogahang; Deflita R.N. Lumi (Tumou Tou, 2021)
The purpose of this paper is an effort to understand and raise the role of the regional philosophy of “Torang Samua” created by God as a contribution to the life of religious moderation in North Sulawesi. In this paper, the researchers examine the philosophy of 'Torang Samua' created by God which was initiated by Olly Dondokambey and Steven Kandouw (ODSK) in the early days of their leadership as Governor and Vice Governor of North Sulawesi, which was used as a middle ground in every religious activity that ultimately had an impact. on the growth of a tolerant, open and even moderate community attitude in the plurality of North Sulawesi society. So it can be described that the philosophy of all people created by God is one way to develop the spirit of moderation in the context of religious plurality in North Sulawesi.